New combinations in Cyrtochilum (Orchidaceae: Oncidiinae) - Dalström, Stig (2020)
Two species, originally described as Odontoglossum amphiglottis and Odontoglossum sodiroi are here transferred to Cyrtochilum (Orchidaceae: Oncidiinae), based on molecular data and morphological features, accompanied by brief discussions about their taxonomic background and natural history, and illustrated with line drawings and photographs. Both species were previously considered to be synonyms of C. ramosissimum by the author of this paper and others, due to limited access of type material. But recent field discoveries reveal that a much stouter growth habit and distinctly corymbose inflorescences distinguish O. amphiglottis from C. ramosissimum. In the case of O. sodiroi the smoothly rounded pair of basal lip calli, which are marginally covered externally by the ventral flanks of the column, distinguish this species from C. ramosissimum, which has more or less denticulate basal callus keels on the lip, and where the ventral columnar flanks are marginally placed between these keels.